Information technology service management - Struik, Jeff. (Canada : Toronto Academic Press, 2024)
The book 'IT Service Management' by Jeff Struik is a comprehensive guide on the principles and practices of managing IT services effectively. It delves into the fundamental concepts of IT Service Management (ITSM), highlighting its importance in aligning IT services with business goals. The book covers key frameworks and standards such as ITIL, COBIT, and ISO 20000, providing a solid foundation for IT managers and aspiring IT service managers. It addresses strategic alignment, portfolio flexibility, architecture management, asset management, IT reporting, and resource management. The author, a seasoned cybersecurity professional, uses real-world examples and case studies to equip readers with actionable strategies for optimizing IT service delivery and driving continuous improvement. The intended audience includes IT managers, service managers, and anyone interested in ITSM.
Includes references and index.
Keywords: Information technology -- Management